Awareness of general practitioners toward hypertension management - Ramakant Rawat; Vidya Sagar Ram; Granth Kumar; Amit Varshney; Manoj Kumar; Pankaj Kumar; Navneet Agrawal (Wolters Kluwer Medknow Publications, 2021)
Introduction: The silent killer, hypertension (HTN), is a significant risk factor for cardiovascular disease. In India, HTN has a major public health effect on cardiovascular health and health-care systems. Aim: The present study was aimed to evaluate the awareness of general practitioners (GPs) toward HTN management and also their approach toward management. Materials and Methods: The present study was a questionnaire-based assessment study. A total of 100 GPs were included in the study as our study sample. All the participants were well informed about the study and after that those who were willing to participate were enrolled after obtaining a written informed consent. Results: The common presenting symptoms of hypertensive patients were predominantly morning headache (71%), dizziness (41%), palpitation (39%), and fatigability (29%). Majority (84%) practiced cuff placement method covering about 2/3rd of the arm at heart level. The preferred position while blood pressure (BP) examination of patient by majority of practitioners was while sitting (53%). The number of readings usually taken for measuring BP for each patient was as follows: one (3%), two (42%), and three (55)%. Conclusion: Although GPs in our study are well informed and up to date on certain aspects of HTN diagnosis and treatment, they may still lack an appropriate approach to HTN history taking, diagnosis, and treatment.